2009
DOI: 10.1103/physrevlett.103.165005
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Pedestal Pressure Reduction Induced by a Thermal Transport Enhancement due to Stochastic Magnetic Boundary Layers in High Temperature Plasmas

Abstract: Good alignment of the magnetic field line pitch angle with the mode structure of an external resonant magnetic perturbation (RMP) field is shown to induce modulation of the pedestal electron pressure p e in high confinement high rotation plasmas at the DIII-D tokamak with a shape similar to ITER, the next step tokamak experiment. This is caused by an edge safety factor q 95 resonant enhancement of the thermal transport, while in contrast, the RMP induced particle pump out does not show a significant resonance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
53
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 29 publications
8
53
2
Order By: Relevance
“…At low collisionalities the structure of the footprint patterns is in fair agreement with the "vacuum" topology, however at high collisionalities the splitting of the separatrix is much stronger than predicted, which suggests the presence of a plasma responses that contributes to an enhanced splitting of the separatrix compared to predictions based on vacuum magnetic field line modeling. In H-mode plasmas the radial pressure profile at the plasma boundary is a strong function of q 95 [31] in line with other experiments, e.g. TEXTOR [6].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…At low collisionalities the structure of the footprint patterns is in fair agreement with the "vacuum" topology, however at high collisionalities the splitting of the separatrix is much stronger than predicted, which suggests the presence of a plasma responses that contributes to an enhanced splitting of the separatrix compared to predictions based on vacuum magnetic field line modeling. In H-mode plasmas the radial pressure profile at the plasma boundary is a strong function of q 95 [31] in line with other experiments, e.g. TEXTOR [6].…”
Section: Discussionsupporting
confidence: 55%
“…A strong poloidal and toroidal modulation of plasma temperature and density has been observed on TEXTOR [6,22] and recently also in DIII-D [31]. In the last reference the T e dependence on q 95 was analyzed by means of two diagnostics: Electron cyclotron emission (ECE) and Thomson scattering as shown in figure 2.…”
Section: Introductionmentioning
confidence: 98%
“…Reference [17] concluded that the resonances in the edge pressure were consistent with achieving good alignment of the magnetic field with the perturbation, suggesting the resonant formation of a stochastic layer. However, the results from JET presented in this Letter are not consistent with this interpretation, as demonstrated in Fig.…”
mentioning
confidence: 98%
“…On DIII-D, strong dependence of the edge pedestal electron pressure on the edge safety factor q 95 has been observed in high confinement, high rotation plasmas during application of an n ¼ 3 field [17]. Reference [17] concluded that the resonances in the edge pressure were consistent with achieving good alignment of the magnetic field with the perturbation, suggesting the resonant formation of a stochastic layer.…”
mentioning
confidence: 99%
“…In DIII-D, RMPs eliminate ELMs by reducing the pedestal pressure gradient below the peeling-ballooning stability limit 6 and by increasing particle transport [7][8][9] and electron thermal transport in low collisionality plasmas. 10 The density pump-out ranges from 5% to 30% as a percentage of the line averaged density in the ELMing H-mode prior to the application of the RMP coils. It is critical to understand the increase in particle transport as a result of RMPs, in order to limit the density pump-out to achieve the maximum plasma performance in future fusion devices.…”
mentioning
confidence: 99%